2019
DOI: 10.18203/2320-6012.ijrms20192494
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and immunological responses of zidovudine lamivudine-nevirapine versus tenofovir lamivudine-efavirenz antiretroviral treatment among HIV-1 infected adults: Gandhi Hospital, Telangana, India

Abstract: Background: HAART (Highly active antiretroviral therapy) is the cornerstone of management of patients with HIV infection. Antiretroviral therapy was started in the year 1986 with the first drug Zidovudine (ZDV). Later on, other antiretroviral drugs (NRTIs, NNRTIs and Pls) were introduced. Dual and mono therapies were used initially but the problem of resistance emerged. Currently, 3 or more ARV drugs are recommended globally for the treatment of people with HIV infection.Methods: A cross-sectional descriptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…A study in Uganda reported that the prevalence of anemia is lower among PLHIV taking a tenofovir-based regimen (11%) than those taking a zidovudine-based regimen (13%) (4). Another study in India found the anemia prevalence among PLHIV taking tenofovir lamivudine efavirenz (TLE) is lower (8%) than those taking zidovudine lamivudine nevirapine (20%) combination regimen (5). Study in Ethiopia stated that anemia prevalence among PLHIV taking tenofovir is 13.20% and among those taking zidovudine is 20.31% (6).…”
Section: Introductionmentioning
confidence: 99%
“…A study in Uganda reported that the prevalence of anemia is lower among PLHIV taking a tenofovir-based regimen (11%) than those taking a zidovudine-based regimen (13%) (4). Another study in India found the anemia prevalence among PLHIV taking tenofovir lamivudine efavirenz (TLE) is lower (8%) than those taking zidovudine lamivudine nevirapine (20%) combination regimen (5). Study in Ethiopia stated that anemia prevalence among PLHIV taking tenofovir is 13.20% and among those taking zidovudine is 20.31% (6).…”
Section: Introductionmentioning
confidence: 99%